IbM PEMBERDAYAAN KELOMPOK PENGRAJIN BATIK KECAMATAN LENDAH KABUPATEN KULONPROGO DIY - Sulistiyono, Bambang; Wahyu Suprapti, Sri Budiwati (Jurnal Bulletin, 2017)
IbM Empowerment of Batik Craftsmen Group Lendah District Kulonprogo DIY. In the development of batik has become a diverse commodity of today's needs such as fashion, complementary elements of the interior is always cultivated to follow the trend of fashion. The starting point of the empowerment of batik craftsmen groups is an increase in the potential they already have, meaning that no batik craftsmen are completely powerless, given a little touch of knowledge / training will be able to use the power of reason to be developed on their own. What distinguishes batik Lendah subdistrict with other batik products is in the technique of gradation staining and batik cloth product patterns.The main target targeted in empowering the group of batik craftsmen is how to improve the skills and knowledge of the group of participants to be able to create design patterns and patterns and colors so that the resulting product will be able to attract consumers to buy it. Increased marketing of products and increased accessibility in terms of product marketing information, so that the continuity of production will be able to eliminate the production mode based on orders alone. This is where the need for continuous assistance in the field of marketing, especially the application of marketing concepts that they have not done. The achievement of theÂ  Program Kemitraan Masyarakat (PKM) for this group of batik craftsmen is the creation of more patterned patterned motifs and designs that can make the distinctiveness of Lendah Kulonprogo batik, thus becoming the main attraction for the consumers (tourists) who will visit Kulonprogo